2021
DOI: 10.1080/00288306.2021.1990088
|View full text |Cite
|
Sign up to set email alerts
|

Porosity and permeability evolution in the Tuaheni Landslide Complex at Hikurangi margin from IODP Sites U1517 and U1519

Abstract: Several mechanisms involving excess pore pressure related to gas hydrate have been proposed to explain active creeping at landslides such as the north Hikurangi margin Tuaheni Landslide Complex (TLC). Cores and logging data were retrieved by the International Ocean Discovery Program (IODP) Expeditions 372 and 375 from the South TLC at Site U1517. Here, the evolutions of porosity, pore structure and permeability are determined to assess the compaction state in the landslide and compare it with that of the undef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…Dutilleul et al. (2022) showed that the base of the Tuaheni landslide coincides with a zone of anomalous porosity, which they attributed to a combination of lithology and elevated pore pressure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dutilleul et al. (2022) showed that the base of the Tuaheni landslide coincides with a zone of anomalous porosity, which they attributed to a combination of lithology and elevated pore pressure.…”
Section: Resultsmentioning
confidence: 99%
“…In other instances, contrasts of hydrogeologic properties across a pronounced lithologic boundary allow pore pressure to build up along a potential failure plane (e.g., Stegmann et al, 2007). Dutilleul et al (2022) showed that the base of the Tuaheni landslide coincides with a zone of anomalous porosity, which they attributed to a combination of lithology and elevated pore pressure. Surprisingly, we found no evidence at Site U1517 for pronounced compositional variations within or across any of the weak layers or inferred slip surfaces.…”
Section: Implications For Slope Stabilitymentioning
confidence: 99%
“…It has been shown that in clay‐rich sediments such as those drilled at Site C0002, the water structurally bound to the clay particles affects the porosity measurements, resulting in biased porosity–velocity relationships (Brown & Ransom, 1996; Tudge & Tobin, 2013). Here, we measure cation exchange capacity (CEC) on core samples to differentiate the clay‐bound water content from the effective porosity (representative of the compaction state of the sediments) from the total porosity routinely measured during the cruises (Conin et al., 2012; Dutilleul, Bourlange, Conin, et al., 2020; Dutilleul, Bourlange, & Géraud, 2021; Dutilleul, Bourlange, Géraud, et al., 2020, 2021; Henry, 1997; Henry & Bourlange, 2004). Then, we propose a modified version of the Erickson‐Jarrard model (Erickson & Jarrard, 1998) fitting better the V p –porosity crossplot using effective porosity and shipboard mineralogical data.…”
Section: Introductionmentioning
confidence: 99%